Design and Construction of an Off-Grid Solar Power Plant (PLTS) Prototype as an Electrical Energy Supply for Booster Pumps in Fish Pond Filtration Systems - Kadhafi, Muamar; Khaeri, Achmad Nur (Peneliti.net, 2025)
This study aims to design and construct a prototype of an off-grid Solar Power Plant (PLTS) as an electrical energy source for booster pumps used in fish pond filtration systems. The system is engineered to continuously supply a 12 Watt load for 24 hours. Testing was conducted under two weather conditions: clear and rainy. The results indicate that solar radiation intensity significantly influences the solar panel output. Under clear weather, the output was more optimal compared to rainy conditions. The battery, used for energy storage, was utilized up to approximately 60% of its total capacity. The system has demonstrated its potential as an alternative power supply solution for fish pond filtration systems.